Pharmacological Profile of Quinoxalinone - Youssef Ramli; Ahmed Moussaif; Khalid Karrouchi; El Mokhtar Essassi (Journal of Chemistry)
Quinoxalinone and its derivatives are used in organic synthesis for building natural and designed synthetic compounds and they have been frequently utilized as suitable skeletons for the design of biologically active compound. This review covers updated information on the most active quinoxalinone derivatives that have been reported to show considerable pharmacological actions such as antimicrobial, anti-inflammatory, antidiabetic, antiviral, antitumor, and antitubercular activity. It can act as an important tool for chemists to develop newer quinoxalinone derivatives that may prove to be better agents in terms of efficacy and safety.